Differential processing of natural scenes in posterior cortical atrophy and in Alzheimer’s disease, as measured with a saccade choice task - Boucart, Muriel; Calais, Gauthier; Lenoble, Quentin; Moroni, Christine; Pasquier, Florence (Frontiers in Integrative Neuroscience, 2014)
Though atrophy of the medial temporal lobe, including structures (hippocampus and parahippocampal cortex) that support scene perception and the binding of an object to its context, appears early in Alzheimer disease (AD) few studies have investigated scene perception in people with AD. We assessed the ability to find a target object within a natural scene in people with typical AD and in people with atypical AD (posterior cortical atrophy). Pairs of colored photographs were displayed left and right of fixation for one second. Participants were asked to categorize the target (an animal) either in moving their eyes toward the photograph containing the target (saccadic choice task) or in pressing a key corresponding to the location of the target (manual choice task) in separate blocks of trials. For both tasks performance was compared in two conditions: with isolated objects and with objects in scenes. Patients with atypical AD were more impaired to detect a target within a scene than people with typical AD who exhibited a pattern of performance more similar to that of age-matched controls in terms of accuracy, saccade latencies and benefit from contextual information. People with atypical AD benefited less from contextual information in both the saccade and the manual choice tasks suggesting a higher sensitivity to crowding and deficits in figure/ground segregation in people with lesions in posterior areas of the brain.